Putin's strategic culture, climate crisis, and power transition : from permafrost to 'permawar' - Skak, Mette (Routledge, 2026)
This book offers a new perspective on the security policy of Russia, linking the Ukraine war with its climate policy and Putin's strategic culture.It offers an analysis of Russian strategic culture, Putin's strategic culture and operational code, as well as "Putinism" being the mental underpinning of Kremlin practices at home and abroad. The volume also addresses Russia's evolution during Putin's years in power and reflects upon Russia's global standing, for example, with respect to China. The work stresses the dialectics between Russia's ideational geopolitics and its climate policy and energy geo-economics, employing a broad approach to understanding security. A secondary analytical concern of the book is the implications and options of Putin's code for European security and world order. The book offers a synthesis of various fields of research and draws on key works by other scholars to offer an overview of the evolving transition of the Russian state into climate denial and militarism.This book will be of much interest to students of Russian security policy, strategic culture, and international relations.
Keywords: National security -- Russia (Federation); Russia (Federation) -- Politics and government.; Russia (Federation) -- Military policy.; elektronické knihy; electronic books